2018
DOI: 10.1590/1516-3180.2018.0022170418
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of praxis test from Cambridge Cognitive Examination (CAMCOG) for Alzheimer’s disease: a cross-sectional study

Abstract: BACKGROUND: Praxis impairment may be one of the first symptoms manifested in dementia, primarily in cortical dementia. The Cambridge Cognitive Examination (CAMCOG) evaluates praxis, but little is known about the accuracy of CAMCOG for diagnosing dementia. The aims here were to investigate the accuracy of praxis and its subitems in CAMCOG (constructive, ideomotor and ideational subitems) for diagnosing Alzheimer's disease (AD) among elderly patients. DESIGN AND SETTING: Cross-sectional study on community-dwelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(65 reference statements)
1
1
0
3
Order By: Relevance
“…Two variables, staging and cognitive performance, influenced the progress of the condition in this sample. [30][31][32][33][34][35][36] As AD is a neurodegenerative condition, the significant relationship between MMSE and FAQ in this study (p<0.001) also agrees with studies reported in the literature, considering that the evolution of this condition is marked by the progression of cognitive deficit in these aged individuals. Sobral et al 36 reported a significant relationship between the MMSE score and CDR, which corroborates our results, confirming cognitive worsening with disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…Two variables, staging and cognitive performance, influenced the progress of the condition in this sample. [30][31][32][33][34][35][36] As AD is a neurodegenerative condition, the significant relationship between MMSE and FAQ in this study (p<0.001) also agrees with studies reported in the literature, considering that the evolution of this condition is marked by the progression of cognitive deficit in these aged individuals. Sobral et al 36 reported a significant relationship between the MMSE score and CDR, which corroborates our results, confirming cognitive worsening with disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…Cardoso et al [ 31 ] demonstrated that individuals with AD who received a supranutritional amount of Se demonstrated a subtle but significant improvement in MMSE, which was associated with an increase in CSF Se levels. Moreover, Cardoso et al [ 30 ] observed that individuals with MCI daily supplemented with Se through Brazil nut intake demonstrated positive responses to certain cognitive functions, such as verbal fluency (storage capacity of the semantic memory system, the ability to retrieve information stored in memory, and the processing of executive functions [ 52 ]), and constructive praxis (to assess an individual’s motor, visuospatial, and visuoconstructive skills [ 53 ]). When Se supplementation was associated with other nutrients, patients with AD also demonstrated a small improvement in memory performance [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Um tópico importante a ser destacado corresponde à função executivapraxia. A função praxia pode ser utilizada como forma de rastreamento confiável para demência subcortical e o comprometimento desta função fornece dados prognósticos mais precisos para o declínio cognitivo e para a incapacidade funcional (CECATO et al, 2018).…”
Section: Discussão 6 Discussãounclassified
“…Os escores totais da praxia e da forma construtiva tiveram diferenças significativas (p<0,0001) entre idosos saudáveis e pacientes com DA; além disso tanto a praxia total quanto a forma construtiva podem classificar os estágios de demência (casos leves e moderados) (CECATO et al, 2018 Síndrome demencial é um fator determinante forte para institucionalização, independente da presença de outras doenças crônicas, perfil sociodemográfico e incapacidade funcional, com taxa de até 61% da população observada por 3 anos (AGÜERO-TORRES et al, 2001). A institucionalização também pode ser consequência da carga de estresse do cuidador que tem fatores positivamente modificáveis associados, como a maior carga para o cuidador e não modificáveis, como idade avançada, estado profissionalmente ativo e maior nível de escolaridade do cuidador (VANDEPITTE et al, 2018).…”
Section: Discussão 6 Discussãounclassified
See 1 more Smart Citation